Fenomena Quiet Firing di Era Kerja Modern: Upaya dan Tantangan Perlindungan Hak Pekerja Dalam Hukum Ketenagakerjaan Indonesia - Achmad Fahrurrozi; Siti Kunarti; Sugeng Santoso PN (JURNAL PENELITIAN SERAMBI HUKUM, 2026)
Abstract Developments in the modern workplace driven by digitalization, work flexibility, and changes in industrial relations have given rise to the phenomenon of “quiet firing”, a practice in which employers indirectly encourage employees to resign without going through formal termination procedures. This study aims to analyze the legal protection mechanisms for workers experiencing quiet firing and to assess the effectiveness and challenges of such protections within Indonesia’s labor law system. The research method employed is a normative legal approach, utilizing legislative, conceptual, and doctrinal frameworks through a literature review. The research findings indicate that although quiet firing is not explicitly regulated, legal protection for workers can be obtained through internal company mechanisms, the role of labor unions, industrial relations dispute resolution, labor inspection, and lawsuits filed with the Industrial Relations Court. However, the effectiveness of such protection still faces various obstacles, particularly the difficulty of proving the case, limited access to internal company evidence, and the absence of specific regulations regarding constructive dismissal. Therefore, regulatory updates are needed to provide legal certainty and more effective protection for workers. Keywords: Quiet Firing, Legal Protection, Labor Law